Changes in plasma enzyme levels following fetotomy and caesarean operation in buffaloes affected with dystocia - PRABHAKAR, S; NANDA, A S; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2023)
The enzymatic activity in twenty-six dystocia-affected buffaloes was studied. Out of 26, 10 buffaloes weretreated through fetomy and 16 buffaloes were subjected to caesarean section. The enzyme levels of six nonnallycalved buffaloes were taken as control. Plasma LOH, ALT and ACP activity were elevated non-significantly,however, plasma AST levels were significantly higher in dystocia affected buffaloes as compared to nonnallycalved control. Plasma AKP levels were considerably low in dystocia group as compared to control. Plasma LDH,AKP and ACP activity were comparatively higher in caesarean conducted buffaloes as compared to fetotomygroup, whereas plasma AST and ALT activity was higher in fetotomy groups than the caesarean operation. Theactivity ofLDH, AST, ALT and ACP remained elevated on post-treatment days in both dystocia affected groupsindicating stress of surgery and tissue ~age with possible necrosis of uterine musculature.
Keywords: Buffalo; caesarean; dystocia; enzymes; fetotomy